2010
DOI: 10.1097/ogx.0b013e3181d0fe5d
|View full text |Cite
|
Sign up to set email alerts
|

Home Versus Hospital Birth—Process and Outcome

Abstract: After completion of this educational activity, the participant should be better able to assess perinatal outcomes described in the reported literature associated with home births in developed countries, list potential advantages and disadvantages of planned home births, and identify confounders in current literature that impact our thorough knowledge of home birth outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 37 publications
0
21
0
1
Order By: Relevance
“…33 The difference between the base rates of 0.4 and 1.7 perinatal deaths per 1000 births goes some way towards explaining the Wax et al finding of a tripled risk. 46 The Wax et al 46 study has generated findings that have been challenged on several points. The first point concerns the comparison of home birth outcomes between countries that vary in culture, geography and healthcare systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…33 The difference between the base rates of 0.4 and 1.7 perinatal deaths per 1000 births goes some way towards explaining the Wax et al finding of a tripled risk. 46 The Wax et al 46 study has generated findings that have been challenged on several points. The first point concerns the comparison of home birth outcomes between countries that vary in culture, geography and healthcare systems.…”
Section: Discussionmentioning
confidence: 99%
“…29 Wax et al undertook a meta-analysis of perinatal mortality in planned home births compared with planned hospital births. 46 The study included 12 studies from seven western countries reporting that less medical intervention during planned home birth is associated with a tripling of the neonatal mortality rate. The study's findings are based on a standard perinatal mortality rate of 0.4 deaths per 1000 births for term infants in the absence of congenital abnormality.…”
Section: Discussionmentioning
confidence: 99%
“…To date this interest has mainly been incidental to other concerns, such as women's choice of place of birth 21 or the development of midwife-led services outside OUs. [22][23][24][25][26] Other work in this area has focused on midwives rather than women and explored the effects on midwives of working in the community 19,27 or in midwife-led units [28][29][30] rather than in consultant-led units. In addition, much of the wider work in health care that has explored problems of space and place has done so while focusing on workplace relationships, for example health-care professionals' relationships with managers 31 and midwives' relationships with junior doctors 32 and support staff.…”
Section: Development Of Birth Centresmentioning
confidence: 99%
“…As a result of this distrust most African Americans are seeking the spiritual and cultural rituals of the African culture (Ngomane and Mulaudzi, 2010). Finally, in our study, the most pertinent factors identified by African American women who desired a home birth were the desire to have control, avoiding pharmacological pain relief, and dissatisfaction with the medical aspects of intrapartum care (Wax et al, 2010;Ngomane and Mulaudzi, 2010;Draper, 2002). The aforementioned are the focus of our literature review.…”
Section: An Afrocentric/africentric Sociological Approachmentioning
confidence: 87%